A parallax view of type 1 diabetes. (12th April 2021) - Weaver, Staci A.; Felton, Jamie L.; Evans-Molina, Carmella
Abstract : The year 2021 marks the 100th anniversary of the discovery of insulin, a therapy that transformed type 1 diabetes (T1D) from a once fatal diagnosis into a chronic condition that can be successfully managed with exogenous insulin administration. In this article, we celebrate the remarkable journey that led to the discovery of insulin and our subsequent understanding of T1D as a disease of immune-mediated β-cell destruction. Further, we discuss an alternative and parallax view of disease development, highlighting maladaptive β-cell responses that act to amplify immune responses and have been implicated in diabetes development.